2013
DOI: 10.3892/br.2013.101
|View full text |Cite
|
Sign up to set email alerts
|

Association between regulating synaptic membrane exocytosis 2 gene polymorphisms and degenerative lumbar scoliosis

Abstract: Abstract. Degenerative lumbar scoliosis (DLS) is a spinal deformity that develops after skeletal maturity and progresses with age. In contrast to adolescent idiopathic scoliosis, the genetic association of DLS has not yet been elucidated. The purpose of this study was to investigate the association between regulating synaptic membrane exocytosis 2 (RIMS2, OBOE) gene polymorphisms and DLS. Two coding single-nucleotide polymorphisms [rs2028945 (Gln1200Gln) and rs10461 (Ala1327Ala)] of RIMS2 were selected and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It is located on the presynaptic membrane and belongs to the regulators of the release of neurotransmitters, on which the transmission of a nerve impulse depends. Polymorphisms in this gene have been found to be associated in humans with the development of degenerative lumbar scoliosis [ 34 ]. In [ 35 ], the authors revealed an association of mutations in the RIMS2 gene with the development of neurodegenerative disorders and pancreatic damage, accompanied by a decrease in insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…It is located on the presynaptic membrane and belongs to the regulators of the release of neurotransmitters, on which the transmission of a nerve impulse depends. Polymorphisms in this gene have been found to be associated in humans with the development of degenerative lumbar scoliosis [ 34 ]. In [ 35 ], the authors revealed an association of mutations in the RIMS2 gene with the development of neurodegenerative disorders and pancreatic damage, accompanied by a decrease in insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…[ 20 22 ] Since it acts as an important modulator of synaptic membrane exocytosis, previous studies typically focused on its functional role in brain-associated diseases. [ 23 25 ] A few studies reported its potential involvement in tumor biology. [ 26 , 27 ] However, some of its interacting proteins have well-characterized regulatory effects on breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…RIMS2 , known to be involved in the synapse-related processes, is one of the genes with higher mRNA expression levels with age. More specifically, RIMS2 is a presynaptic protein in the synaptic vesicle release site, so called the active zone, and interacts with several synaptic proteins including Rab3 to regulate Ca 2+ -dependent neurotransmitter release from synaptic vesicles 21,22 . Previous study suggested that ageing may decrease the active zone density of neuromuscular junctions in mice and rats which may affect neurotransmission 23 .…”
Section: Discussionmentioning
confidence: 99%